High gain UWB horn antenna for concealed metal detection and microwave imaging application - Shaikh, Faraz Ahmed; Khan, Sheroz; Alam, Zahirul; Hassan Abdalla Hashim, Aisha; Badron, Khairayu; Yaacob, Mashkuri; Shahid, Zeeshan (2017)
This paper is about a discussion of detection technology and imaging system employed for the recognition of metal inside and between two walls. The UWB frequency (3.1Ghz to 10.6Ghz) is produced by ground-generating radar (GPR). The working principal for detection system is based on Time Domain Reflectometry (TDR) using through wall imaging (TWMI). This paper is presented as a unique scheme of detection of wall and distance between walls. Vector Network Analyzer (VNA) is used to generate very small duration pulses for illuminating the wall, behind and between two walls under investigation is an UWB probe array system. The simulation results of horn antenna have shown an enormous capacity for penetration in order to recognise a hidden metal placed between two walls and estimate the gap width with fine accuracy, proving to be an attractive development in the detection and imaging system technology. In order to improve the resolution of an image, better quality filters have been developed and implemented.